(untitled) (Swiss Medical Weekly, 2011)
PRINCIPLES: Statin therapy reduces cardiovascular morbidity and mortality. However, a substantial residual cardiovascular risk can be observed in patients receiving this therapy due to persisting lipid abnormalities as well as to the lack of a systematic global risk-reduction strategy. The objective of the study was to assess the prevalence of dyslipidemia in a cohort of patients living in Switzerland and receiving statin therapy. METHODS: This cross-sectional study was conducted by 61 primary care physicians, cardiologists, endocrinologists and internists in Switzerland. Patients were consecutive outpatients ≥45 years-old, on statin therapy for at least 3 months with available lipid values. A clinical examination and a recording of the latest lipid values on statin therapy were performed in all patients. RESULTS: A total of 473 patients (age 66.3 ± 9.41 years; 61.9% male) were included in the final analysis. Under statin therapy, 40% of the analysed patients had a normal lipid profile, 32.6% presented increased low-density lipoprotein cholesterol (LDL-C) (3.35 ± 0.88 mmol/L), 28.8% low high-density lipoprotein-cholesterol (HDL-C) (0.95 ± 0.18 mmol/L) and 31.1% elevated triglycerides (2.69 ± 1.04 mmol/L). It is of note that the included population was characterised by a high prevalence of cardiovascular risk factors (86.5% patients had 10-year cardiovascular risk >20%). Nevertheless, the lipid lowering therapy was modified in only 15.4% of the patients. CONCLUSION: Persistent dyslipidemia is a reality in statin-treated patients and may contribute to their residual cardiovascular risk. Therefore, comprehensive lipid management should be preferred to aggressive LDL-C lowering alone. Moreover, strategies to assess and modify the global cardiovascular risk of patients should be taken into account as an important component of primary and secondary prevention.